2017
DOI: 10.1103/physrevlett.118.174801
|View full text |Cite
|
Sign up to set email alerts
|

Mitigation of the Hose Instability in Plasma-Wakefield Accelerators

Abstract: Current models predict the hose instability to crucially limit the applicability of plasma-wakefield accelerators. By developing an analytical model which incorporates the evolution of the hose instability over long propagation distances, this work demonstrates that the inherent drive-beam energy loss, along with an initial beam-energy spread, detunes the betatron oscillations of beam electrons and thereby mitigates the instability. It is also shown that tapered plasma profiles can strongly reduce initial hosi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
76
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(82 citation statements)
references
References 28 publications
5
76
1
Order By: Relevance
“…We note that the qualitative behavior for ∂ ξ k β < 0, whereby the amplitude of the oscillations initially increases but later decreases, is consistent with the behavior shown in [11], where the authors observed, in numerical simulations, that the deceleration of the tail of driver bunch (which induces ∂ ξ k β < 0) in the blow-out regime could cause a similar decrease in amplitude.…”
supporting
confidence: 89%
“…We note that the qualitative behavior for ∂ ξ k β < 0, whereby the amplitude of the oscillations initially increases but later decreases, is consistent with the behavior shown in [11], where the authors observed, in numerical simulations, that the deceleration of the tail of driver bunch (which induces ∂ ξ k β < 0) in the blow-out regime could cause a similar decrease in amplitude.…”
supporting
confidence: 89%
“…A remedy for mitigation of the hose instability for the drive bunch was suggested in Ref. [15]. It is based on tapering of plasma density at the input and the output of a plasma channel.…”
Section: Instabilitymentioning
confidence: 99%
“…We would like to stress that until ways to overcome this limit are found, plasma-based collider schemes remain impractical from the perspective of acceleration efficiency. The BBU (also known as the hose) instability in PWFA concepts has been considered previously only for drive bunches [14,15]. Although these considerations are important, the quality of the drive ♦ E-mail: val@fnal.gov bunch (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…A number of methods have been suggested for mitigating the PWFA transverse instabilities. As discussed in [26,27] they may be grouped into three; reduction of instability seed [31]; disruption of the coherence and reduction of the beam-plasma coupling. Disruption of the coherence can be done in a variety of ways.…”
Section: Transverse Instabilitiesmentioning
confidence: 99%